1997
DOI: 10.1128/jb.179.3.889-898.1997
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen regulation of growth, growth yields, and methane gene transcription in Methanobacterium thermoautotrophicum deltaH

Abstract: Changes in growth rate, methanogenesis, growth yield (Y CH4 ), and methane gene transcription have been correlated with changes in the supply of H 2 to Methanobacterium thermoautotrophicum ⌬H cells growing on H 2 plus CO 2 in fed-batch cultures. Under conditions of excess H 2 , biomass and methanogenesis increased exponentially and in parallel, resulting in cultures with a constant Y CH4 and transcription of the mth and mrt genes that encode the H 2 -dependent N 5 ,N 10 -methenyltetrahydromethanopterin (methen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
121
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(131 citation statements)
references
References 44 publications
10
121
0
Order By: Relevance
“…Comparison with our results suggests that both effects may have occurred, and that similar patterns of gene expression may occur in diverse species of methanogens. Among those genes of methanogenesis that we found to be markedly up-regulated by hydrogen limitation in M. maripaludis, studies in Methanothermobacter thermautotrophicus (4,22) led to a similar conclusion for homologs of Mtd, methylenetetrahydromethanopterin reductase, (24). In batch culture low hydrogen coincides with low growth rate, and the effects may have been a result of growth rate differences, consistent with our observation in M. maripaludis of decreased hmd mRNA levels with lower growth rate.…”
Section: Real-time Rt-pcrsupporting
confidence: 78%
“…Comparison with our results suggests that both effects may have occurred, and that similar patterns of gene expression may occur in diverse species of methanogens. Among those genes of methanogenesis that we found to be markedly up-regulated by hydrogen limitation in M. maripaludis, studies in Methanothermobacter thermautotrophicus (4,22) led to a similar conclusion for homologs of Mtd, methylenetetrahydromethanopterin reductase, (24). In batch culture low hydrogen coincides with low growth rate, and the effects may have been a result of growth rate differences, consistent with our observation in M. maripaludis of decreased hmd mRNA levels with lower growth rate.…”
Section: Real-time Rt-pcrsupporting
confidence: 78%
“…Thus, methane formation and growth become more tightly coupled under conditions of reduced hydrogen availability. This finding is in agreement with observations by others (7,8,14,17,18,27,33), although the hydrogen concentrations had not been explicitly measured by those authors. A novel analytical approach applied to fed-batch growth suggested that Y CH4 max can take two distinct values, approximately 3 and 7 g mol Ϫ1 of methane, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…However, growth experiments with media containing all biological relevant trace elements in excess seem to rule out this possibility. Quite remarkably, a shift toward linear growth was always also preceded by discrete decreases of the specific methane-forming activity at the end of the exponential phase in cultures supplemented with the complete trace set of elements (Table 1 (14) demonstrated that mrt and hmd were expressed during exponential growth, whereas mcr and mdh transcripts were observed when the growth rate declined and the rate of methanogenesis became constant, which is typical for linear growth. It remains to be verified, however, if the differential expression of the above and other methane genes (13,15,16,18,20,34) is connected to hydrogen deprivation, as has often been assumed, or to the shift in growth phases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of M. thermautotrophicus mRNA-Six cultures of M. thermautotrophicus were grown in 1.5-liter bioreactors at 55°C in a minimal salts medium (24). A gas mixture of 89% H 2 , 11% CO 2 was supplied to the cultures at a flow rate of 200 ml/min.…”
Section: Methodsmentioning
confidence: 99%